Obtenção de membrana cerâmica porosa a partir da utilização do resíduo de caulim como matéria-prima alternativa e da serragem da madeira como agente porogênico - Ferreira, Chrystiano Araujo (2019)
Several efforts have been made in recent years in the development of ceramic membranes from low-cost raw materials. The reuse of kaolin waste is shown as an alternative to less environmental impact and economic interest. The treatment of this waste by hydrocyclone appears as an efficient alternative for its adequacy to the ceramic production cycle, being able to have applicability in the production of ceramic membranes. The development of interconnected pores in ceramic membranes is due to the introduction of pore-forming agents, normally organic, thus, studies of the use of wood sawdust waste as pore-forming agents in order to provide adequate porosity, combined with a high permeate flow and low depreciation of mechanical strength are also essential. The work has, therefore, the objective of studying and developing porous ceramic membranes from the use of fine (FF) and coarse (FG) fractions resulting from the hydrocyclone of the fine kaolin waste (RCF), using wood sawdust waste as pore-forming agent. The work involved initially the hydrocyclone of the RCF and the mineralogical, chemical, thermal and granulometric characterization of the RCF, FF, FG and, of the clay. Then, studies were carried out between two types of sawdust wastes in a comparative manner in relation to the moisture content, grain size by sieving, fire loss and the appropriate percentage, thus defining the type, retained in sieve and percentage more adequate to obtain the ceramic membranes. Five formulations were analyzed technologically by varying the ratio of FF and FG in obtaining ceramic membranes in disk form and at three firing temperatures: 1150 ° C, 1200 ° C and 1250 ° C. At the end, the obtained membranes were characterized in a mineralogical and morphological manner and evaluated the properties of permeate flow and compressive strength. The results indicate that the membrane of formulation D (3FG:1FF) presented the best results, with the highest compressive strength, 28.65 MPa at 1200 ° C, however, with pores above 10 μm, limiting it to applications such as filtration.